PEMBERDAYAAN POTENSI MASYARAKAT PENERIMA BANTUAN ZAKAT PRODUKTIF DALAM UPAYA OPTIMALISASI PENDAPATAN USAHA DI KOTA GORONTALO - HM, Muhdar.; Muhajir Kadim , Immawan (Al-Buhuts, 2023)
The aim of this research is to describe the potential of productive zakat recipient communities in their efforts to develop their businesses; designing an effective empowerment model for productive zakat recipients; and redesigning effective efforts to optimize business revenues through training models. The methods used are observation, interviews, FGD, and empowerment. The research results show that productive zakat recipients have enormous potential to develop their businesses. The potential empowerment model for productive zakat recipients is grouped into two stages. (1) providing business capital in the form of goods worth Rp. 3,000,000 (three million rupiahs). (2) providing additional business capital in the form of goods worth Rp. 2,000,000 (two million rupiahs), in this second stage it will be given to people (mustahik) whose businesses are experiencing growth, while businesses that are not experiencing development will not receive the second stage of capital assistance. (3) Urgent empowerment efforts to optimize the income of businesses receiving productive zakat assistance are to carry out coaching and training patterns, as well as ongoing mentoring